Phenotypic differentiation of Barilius bendelisis (Cypriniformes: Cyprinidae) in four rivers from Central Indian Himalaya - Javaid Iqbal Mir; Neha Saxena; Rabindar Singh Patiyal; Prabhati Kumari Sahoo (Revista de Biología Tropical, 2015)
Barilius bendelisis, commonly known as Indian Hill Trout is an upland water fish of South East Asia. It belongs to the family Cyprinidae and dwells in shallow, clear and cold water. In this study, the intraspecific variation of Barilius bendelisis, on the basis of morphometric characters, was investigated. Altogether, 402 specimens were collected from four rivers in the Central Indian Himalaya. A truss network was constructed by interconnecting 12 landmarks to yield 30 distance variables that were extracted from digital images of specimens using tpsDig2 and PAST software. Allometric transformed truss measurements were subjected to univariate analysis of variance, factor analysis and discriminant analysis. All variables exhibited significant differences between the populations. Altogether 88% of the specimens were classified into their original populations (81.98% under a ‘leave-one-out’ procedure). With factor analysis measurements of the head region, the middle portion and the caudal region had high loadings on the first and second axis. The results indicated that B. bendelisis has significant phenotypic heterogeneity between the geographically isolated regions of Central Indian Himalaya. We hypothesize that the marked interspecific variation in B. bendelisis is the result of local ecological conditions.